PHYSICAL EDUCATION IN EUROPE (Fiep Bulletin - online, 2012)
After some terminological as well as conceptual precisions about the use of the concepts ?Physical Education? (PE) and ?Sport? in his lecture, the author gives a description of the actual evolution of school physical education in Europe, with new concepts and ideas on PE mainly for children aged 4 to 11 years and with a somewhat idealistic summary of the objectives or aims, the contents and the teaching methods of European PE resulting of the study of the publications of mainly French and German authors in the field of modern Didactics or theory of PE. It tries to reflect the very complex situation of European PE in an intercultural, global perspective, beyond the frontiers and the official texts ruling PE in the 48 European countries.This idealistic view is completed by the data collected by Prof. Ken Hardman in his ?European Physical Education/Sport Survey? realized for the Committee for the Development of Sport (CDDS) of the Council of Europe in 2001. The most interesting data of this Survey about national, state or regional PE as a compulsory curriculum subject as well as about the facilities, the equipment, with also inadequate facilities and maintenance in different countries are reproduced. The same is true for the qualification and the training of the teaching personnel in PE in the different European countries and specific issues about concerns, problems in to-days PE as well as the perspectives for PE in Europe. Hardman‘s as well as other recent international surveys have revealed that PE in schools has experienced marginalisation also in European countries. This has lead to the comment ?…that the crux of PE in Europe is that there is too much of a gap between the promise and the reality? (Deputy Secretary General of the Council of Europe) and that solutions have to be found ?to assist in the process of conversion of ?promises‘ into ?reality‘ and so meet with the challenges posed by exercise deficiency and obesity-related risks? (Ken Hardman).
Keywords: PE in Europe; CDDS